The Effect of Astaxanthin on Glutathione Levels in Damaged Liver Tissues of Male Wistar Rats Induced By Oral Formaldehyde - ., Andriani; Halim, A; Handini, M; Armyanti, I; Novianry, V (KnE Life Sciences, 2019)
Formaldehyde is an aldehyde derivative which is illegally used as a food preservative. An impaired liver function could result from exposure to formaldehyde through the process of oxidative stress. Astaxanthin is expected to increase the levels of glutathione (GSH), which is a natural antioxidant in the human body. An antioxidant can be used to inhibit formaldehyde-induced free radicals. This study aimed to determine the effect of astaxanthin on GSH levels in damaged liver tissues of male Wistar rats induced by oral formaldehyde. This study was an experimental study with a posttest-only control group design. Thirty rats were divided into normal control group; the negative control group which was given only formaldehyde; Group 1, 2, and 3 which was given a 12, 24, and 48 mg/day dose of astaxanthin. GSH levels of each group were measured using the Ellman Method and the data were analyzed statistically using SPSS 23.00. The value of GSH levels in treatment group 1 was 4.492 ± 0.29 µg/ml, treatment group 2 was 6.075 ± 0.96 µg/ml, and treatment group 3 was 5.132 ± 0.52 µg/ml. GSH levels in group 2 and 3 were significantly different compared with the negative control group (LSD,p<0.05).However, GSH levels in group 1 were not significantly different compared with the normal control group and negative control group (LSD, p>0.05). Astaxanthin could increase GSH levels in damaged liver tissues of male Wistar rats induced by oral formaldehyde. Keywords: astaxanthin, formaldehyde, glutathione